Slower information processing speed is associated with persistent burnout symptoms but not depression symptoms in nursing workers. Issue 1 (2nd January 2021) - Potter, Guy; Hatch, Daniel; Hagy, Hannah; Radüntz, Thea; Gajewski, Patrick; Falkenstein, Michael; Freude, Gabriele
ABSTRACT: Introduction : Burnout and depression both occur with chronic work-related stress, and cognitive deficits have been found when symptom severity results in work disability. Less is known about cognitive deficits associated with milder symptoms among active workers, and few studies have examined whether cognitive deficits predict persistent burnout and depression symptoms. The goal of this study was to examine the association of information processing speed and executive function performance to burnout and depression symptoms at baseline and 12-month follow-up in a sample of actively working individuals (N = 372). Method : The design was prospective with laboratory cognitive data at baseline, and burnout and depressive symptoms assessed at baseline and monthly follow-ups. Information processing speed and executive functions were assessed in a task-switching paradigm, including single-task reaction time (RT), switching costs, and mixing costs. Burnout was assessed with the Exhaustion subscale of the Oldenburg Burnout Inventory and depression with the Patient Health Questionnaire-9. Results : Slower RT was modestly associated with higher levels of burnout symptoms both cross-sectionally and prospectively, but switching costs and mixing costs were not associated with burnout symptoms. None of the cognitive measures were associated with depression symptoms cross-sectionally or prospectively. Conclusions : Despite statistically significant findings of slowed RT in acute exhaustion-related burnout, the proportion of variance accounted for in the models was small and did not predict clinically significant levels of distress. The absence of statistically significant findings for depression symptoms suggests the cognitive profile associated with the exhaustion dimension of burnout may be distinct from that of depression, which reflects a more heterogeneous symptomatology. Our data suggest the clinical impact of burnout symptoms on actively working individuals is marginal; nonetheless, it is important to screen and intervene on burnout and depression symptoms in the workplace because they can lead to other forms of work impairment.